Effect of naturally occurring napthoquinones on root-knot nematode Meioidogyne javanica - DAMA, L.B. (Indian Phytopathology, 2012)
The effect of naturally occurring napthoquinones were studied in vitro on root-knot nematode, Meloidogyne javanica, at concentration 200 J,Jg110 ml waterlflask containing 100 nematodes exposed for 6 h, 12 hand 24 h. The plumbagin showed 100% mortality, juglone 97.94% and lawsone 58.31% at 24 h exposure. The effect of these napthoquinones were found to be nematicidal on root-knot nematodes.